On the fixed points of iterative contractive mappings defined via implicit relation. (3rd June 2021) - Aksoy, Ümit; Erhan, İnci M.; Fulga, Andreea; Karapınar, Erdal
Abstract : In this paper, we consider an implicit relation to generalize iterative fixed point results in the literature in the context of metric spaces. We conclude that several existing results are immediate consequences of our main results.